Design and construction of an innovative device for corrosion testing of materials in different environments - Garcia-Hernandez, Fernando; Oskam, Adrian; Castano, Victor (Publishing House of Lviv Polytechnic National University, 2009)
Corrosion is the deterioration of a substance (usually a metal) or its properties because of the reaction with its environment. There are many forms of corrosion, some of which are encountered in everyday life. Direct losses due to corrosion are more than $276 billion dollars annually = 3.1% of Gross Domestic Product only in the United States. If we consider the rest of the world this figure would be many times higher. However, corrosion and its control besides of its importance, is often a neglected element in the practice of engineering. This work presents the design of an innovative low cost device to carry out corrosion testing of materials in different environments. High costs that result from the fabrication of special probes or devices for testing, make it an interesting challenge for the engineer or designer. This original and innovative device has been designed accordingly to both the laboratory equipment which will do the characterization and assessment of the corrosion testing, as well as the “Loop reactor” wher testing will be carried out in different environments. Розроблено модель дешевого інноваційного приладу для проведення корозійних тестів в різних середовищах. Показано, що цей оригінальний та новітній прилад може використовуватись як лабораторне обладнання для характеристики і оцінки корозійних тестувань, а також як «петельний реактор», який дає можливість проводити тестування зразків у різних середовищах.
Модель і конструкція інноваційного приладу для проведення корозійних тестів в різних середовищах
Keywords: device design; probes; corrosion; industrial design; testing methods; модель приладу; проби; корозія; промислова розробка; випробування